Towards a characterization of BPM tools' simulation support: the case of BPMN process models - Pereira, José Luís (2019)
Due to the increasing acceptance of BPM (Business Process Management), nowadays BPM tools are extensively used in organizations. Core to BPM are the process modeling languages, of which BPMN is the one that has been receiving most attention these days. Once a business process is described using BPMN, one can use a process simulation approach in order to discover its optimized form. This paper analyzes the business process modeling and simulation areas, identifying I the elements that must be present in the BPMN language in order to allow processes to be simulated. During this analysis a set of existing BPM tools, which support BPMN, are compared regarding their limitations in terms of simulation capabilities. In this context, a platform to support the characterization of BPM tools regarding process simulation capabilities has been developed, which might be useful to users ii ho want to select the most adequate BPM tool taking into account their simulation needs.